DER, ROA AND OPERATING CASH FLOW AGAINST FIRM VALUE IN VARIOUS INDUSTRIAL COMPANIES LISTED ON THE IDX 2015-2019 - Indra Maulana; Anita Wijayanti; Riana Rachmawati Dewi (CAHAYA AKTIVA, 2020)
This study aims to test and analyze the effect of Debt to Equity Ratio (DER), Return On Assets (ROA) and Operating Cash Flow (OCF) on Firm Value as proxied by Price to Book Value (PBV). The population in this study were various industrial sector manufacturing companies listed on the IDX in 2015-2019. Sampling in this study using purposive sampling technique in order to obtain a sample of 9 companies with 45 observations. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that simultaneously DER, ROA and OCF affect firm value. Partially ROA and OCF have a significant effect on firm value, while DER has no effect on firm value. The result of the coefficient of determination (R2) is 0.602, meaning that 60.2% PBV can be explained by DER, ROA, and OCF while the rest is explained by other variables outside of this research model. Keywords: DER, ROA, Operating Cash Flow, PBV